1995
DOI: 10.2331/fishsci.61.915
|View full text |Cite
|
Sign up to set email alerts
|

The Effcet of Combined Use of Several Alternnative Protein Sources in Fingerling Rainbow Trout Diets

Abstract: A feeding experiment was conducted to investigate the effect of combined use of several alternative protein sources for fish meal in diets for fingerling rainbow trout Oncorhynchus mykiss. In the con trol diet, brown fish meal (BFM) was used as the sole protein source to provide 40% crude protein . In the test diets, 60 or 80% of the BFM protein in the control diet was isonitrogenously replaced by several combinations of soybean meal (SBM), meat meal (MM), malt protein flour (MPF), corn gluten meal (CGM), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
0
14
1
Order By: Relevance
“…In contrast, Yamamoto, Unuma, and Akiyama (1995) found that a combination of protein from brown fishmeal, meat meal, and malt protein flour (40:35:25) produced no significant difference from a fishmeal-based diet, but did successfully replace 60% of the fishmeal protein in rainbow trout diets; while a combination of fishmeal, soybean meal, meat meal, malt protein flour, and dried brewer's yeast can replace 80% fishmeal protein without supplementation of crystalline amino acids. Also, growth performance was significantly lower when soybean meal, meat meal , or malt protein flour were used separately.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, Yamamoto, Unuma, and Akiyama (1995) found that a combination of protein from brown fishmeal, meat meal, and malt protein flour (40:35:25) produced no significant difference from a fishmeal-based diet, but did successfully replace 60% of the fishmeal protein in rainbow trout diets; while a combination of fishmeal, soybean meal, meat meal, malt protein flour, and dried brewer's yeast can replace 80% fishmeal protein without supplementation of crystalline amino acids. Also, growth performance was significantly lower when soybean meal, meat meal , or malt protein flour were used separately.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, it is evident from the present study that a blend of fisheries by-product and plant protein with subsequent fermentation is an effective method to utilize alternative protein sources in aquafeeds. Blending of different ingredients is often recommended to achieve balanced nutritional composition and complementary amino acid profiles, and to mask unpalatable substances present in feed ingredients [1,17,[19][20][21]. Fermentation is a technique commonly used in the food industry, and may decrease or eliminate antinutritional constituents from oilseeds [5] and increase bioavailability of nutrients as well as overall nutritional quality [6].…”
Section: Discussionmentioning
confidence: 99%
“…Meat meal, either alone or in combination with other terrestrial protein concentrates such as soybean meal and gluten meal, has been successfully used for the partial replacement of fish meal in diets for cultured carnivorous fish including channel catfish, Ictalurus punctatus (Mohsen & Lovell 1990; Lovell 1992), yellowtail, Seriola quinqueradiata (Shimeno, Masumoto, Hujita, Mima & Ueno 1993; Shimeno, Mima, Imanaga & Tomaru 1993), rainbow trout, Oncorhynchus mykiss (Watanabe, Pongmaneerat, Sato & Takeuchi 1993; Yama moto, Unuma & Akiyama 1995; Bureau et al . 2000), hybrid bass, Morone saxatilis × M. chrysops (Webster, Tiu & Tidwell 1997), sea bream, Sparus aurata (Davies, Nengas & Alexis 1991; Nengas, Alexis & Davies 1999), and European sea bass, Dicentrarchus labrax (Langar & Metailler 1989).…”
Section: Discussionmentioning
confidence: 99%